Dixon Chemical Shift Magnetic Resonance Imaging for Differentiating Benign, Malignant, and Non-Neoplastic Bone Marrow Lesions - Kamel, Zeinab Sobhy; A. Alam Eldin, Mohamed; Elbarbary, Aly Mohamed; Yousef, Mohamed Ahmed; M. Mashaly, Emad (Journal of Neonatal Surgery, 2025)
Background: On magnetic resonance imaging (MRI), bone marrow (BM) lesions cause a localized or widespread change in signal strength or a heterogeneous signal pattern, which results in a steady water signal. Finding out how well Dixon chemical shift imaging distinguishes between benign neoplastic, malignant, and non-neoplastic BM lesions was the goal of this study. Methods: For this prospective investigation, 40 individuals of both sexes with suspicious bone tumors or indeterminate marrow lesions or altered BM signal intensity on T1 and T2 WI. The control group consisted of twenty participants. Every participant in the study underwent an MRI, including the Dixon method. The spine was the most often affected area by bone marrow lesions. Results: The signal dropout % value in benign BM lesions was significantly higher (P<0.05) than in the malignant and control groups. The signal intensity ratio (SIR) of the benign group was significantly lower than that of the malignant and control groups. While signal dropout % sensitivity, specificity, PPV, and NPV were 91.67%, 60.0%, 73.3%, and 80.0%, respectively, SIR's sensitivity, specificity, PPV, and NPV were 91.67%, 75.0%, 84.6%, and 85.7% instead. The receiver operator characteristic for signal drop out percentage yielded an AUC of 0.977, while SIR's gave an AUC of 0.951. Diagnosis accuracy of Dixon MRI in the studied patients was with sensitivity, specificity, PPV, NPV, and accuracy 87.50%, 75%, 84.0%, 80% and 82.50%, respectively. Conclusions: With its quantitative indicators, Dixon MRI is a useful and quick tool for addressing problems. It has a great capacity to distinguish between benign and malignant BM lesions with high diagnostic accuracy, sensitivity, and specificity